Terahertz Absorption Characteristics of the Sodium Carboxymethyl Cellulose Colloid Based on Microfluidic Technology - Ding, Chenxin; Su, Bo; Wang, Guoyang; Meng, Qinghao; Wang, Jiahui; Zhang, Cunlin (International Journal of Optics, 2021)
Sodium carboxymethyl cellulose is a type of macromolecular chemical substance that is widely used in the industry for food thickening. In this study, terahertz and microfluidic technologies were combined, and a microfluidic chip with a channel depth of 50 μm was fabricated to carry samples. The terahertz characteristics of the sodium carboxymethyl cellulose colloid were studied at different concentrations and applied electric fields. The obtained results showed that different concentrations of sodium carboxymethyl cellulose have different time-domain spectra; with an increase in concentration, the terahertz transmittance of sodium carboxymethyl cellulose decreased. Under the applied electric field treatment, the longer the electric field acting time is, the higher the terahertz transmission intensity is. This approach is a safe and reliable new method for the determination of sodium carboxymethyl cellulose concentration, which provides technical support for the in-depth study of sodium carboxymethyl cellulose.